Surgical Treatment of Hyperthyroidism – Experience of the Department of Endocrine Surgery, University Clinical Center Kragujevac - Jakovljevic, Slobodan; Pešović, Jovan; Nešovanović, Duško; Tvrdišić, Vladimir; Marko; Milev, Borka; Juković, Zlata (Medicinski časopis, 2026)
Introduction: Hyperthyroidism represents a significant endocrine disorder, with the most common causes being Graves’ disease (GD), toxic multinodular goiter (TMNG), and toxic adenoma (TA). Surgical treatment occupies an important place in the therapeutic algorithm, particularly in situations where medical therapy or radioactive iodine treatment is contraindicated or ineffective. Objective: To present the experience of the Department of Endocrine Surgery of the University Clinical Center Kragujevac in the surgical treatment of hyperthyroidism during the period 2018–2024. Materials and Methods: A retrospective analysis was conducted of 188 patients operated on for hyperthyroidism, out of a total of 480 patients who underwent surgery for thyroid diseases over a six-year period. The analyzed parameters included diagnosis type, type of surgical procedure, demographic data, incidence of carcinoma on definitive histopathological findings, and postoperative complications. Results: Among the 188 operated patients, 62 had GD, 65 had TMNG, and 61 had TA. In patients with GD, total thyroidectomy was performed in 55 cases and near-total thyroidectomy in 7 cases. In the TMNG group, total thyroidectomy was performed in 60 patients and near-total thyroidectomy in 5 patients. In all 61 patients with TA, lobectomy was performed. The mean age was 48.6 years for GD, 58.3 years for TMNG, and 46.5 years for TA. The female-to-male ratio was 5:1 in GD, 4:1 in TMNG, and 4:1 in TA. Thyroid micropapillary carcinoma was detected in 1 patient with GD, 5 patients with TMNG, and 2 patients with TA. Complications included seroma in 8 patients, hematoma in 4 patients, permanent recurrent laryngeal nerve paralysis in 2 patients, transient recurrent laryngeal nerve paralysis in 5 patients, and transient hypocalcemia in 14 patients. Conclusion: Surgical treatment of hyperthyroidism in our center has demonstrated favorable outcomes with a low rate of serious complications. The results are consistent with contemporary literature and confirm that surgery remains an important therapeutic option in appropriately selected indications.